2018
DOI: 10.1080/23322039.2018.1514929
|View full text |Cite
|
Sign up to set email alerts
|

The impact of economic policy uncertainty on the innovation in China: Empirical evidence from autoregressive distributed lag bounds tests

Abstract: This study is the first attempt to scrutinize the causal relationship between economic policy uncertainty (EPU) and innovation in the case of China, using the autoregressive distributed lag (ARDL) approach to co-integration approach of innovation accounting for causality analysis. The empirical findings show that EPU can negatively affect innovation. EPU indicates a significantly negative impact on innovation as well as on the gross domestic product (GDP) growth rate. The combined results based on ARDL, innova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 66 publications
0
9
0
Order By: Relevance
“…Most scholars rmly believe that changes in local government o cial policies reduce R&D activities, thereby negatively impacting investment in innovation activities (Feng and Johansson 2017). Such decisions also affect future innovation activities (Saleem et al 2018), especially for companies with nancial constraints and those dependent on external nancing (Xu 2020); the conclusions of these studies for the negative effects are contradictory. Through research on the initial public offering (IPO) suspension in China, it was determined that the company's innovation activities were reduced during the suspension period, which was speculated to continue for several years (Cong and Howell 2020).…”
Section: Economic Policy Uncertainty and Green Technology Innovatiomentioning
confidence: 99%
“…Most scholars rmly believe that changes in local government o cial policies reduce R&D activities, thereby negatively impacting investment in innovation activities (Feng and Johansson 2017). Such decisions also affect future innovation activities (Saleem et al 2018), especially for companies with nancial constraints and those dependent on external nancing (Xu 2020); the conclusions of these studies for the negative effects are contradictory. Through research on the initial public offering (IPO) suspension in China, it was determined that the company's innovation activities were reduced during the suspension period, which was speculated to continue for several years (Cong and Howell 2020).…”
Section: Economic Policy Uncertainty and Green Technology Innovatiomentioning
confidence: 99%
“…This finding is clearly a reflection of the weak institutions that are prevalent in Africa as explained in the introductory section of this paper. This finding amplifies the submissions of studies that have shown that terrorism and uncertainty are detrimental to economic performance, especially in developing countries (Çinar, 2017; Ghirelli et al, 2021; Iheonu & Ichoku, 2021; Istiak & Serletis, 2018; Kang et al, 2020; Ogbonna et al, 2022; Saleem et al, 2018). For instance, Ogbonna et al (2022) found that instead of counteracting the negative effect of world uncertainty on FDI inflows in Africa, economic governance institutions on the continent are intensifying it.…”
Section: Resultsmentioning
confidence: 63%
“…Some studies in the extant literature have examined the effect of uncertainty on various economic indicators. For instance, it has been shown that rising uncertainty foreshadows declines in economic growth (Baker et al, 2016; Berger et al, 2017; Caggiano et al, 2017; Čižmešija et al, 2017; Ghirelli et al, 2021; Istiak & Serletis, 2018; Kang et al, 2020; Saleem et al, 2018); plays a primary role in explaining the fluctuations in inflation rates, interest rates and stock prices (Bahmani‐Oskooee & Maki‐Nayeri, 2019; Berger et al, 2017; Jeon, 2018; Mumtaz & Musso, 2021; Rehman & Apergis, 2019a); stimulates volatility in commodity prices, especially oil prices (Bakas & Triantafyllou, 2020; Rehman & Apergis, 2019b; van Robays, 2016); and deters consumption and investment (Baker et al, 2016; Ghirelli et al, 2021; Moore, 2017). Majority of these studies focused predominantly on the advanced economies of United States, Canada, United Kingdom, Europe, China, Japan, Australia and Korea.…”
Section: An Overview Of the Literaturementioning
confidence: 99%
“…Some prior studies have reported that uncertainty significantly affected the number of patents. However, while some of them [20,[53][54][55][56] reported a negative effect, others [7,13,57] have reported a positive influence. We revisited this research topic, based on our country-level sample.…”
Section: Randd Personnel and Patent Applicationsmentioning
confidence: 96%